2021
DOI: 10.2514/1.j060396
|View full text |Cite
|
Sign up to set email alerts
|

Permeable Leading Edges for Airfoil and Fan Noise Reduction in Disturbed Inflow

Abstract: A detailed experimental study on the aerodynamic performance and noise emission of airfoils and fan blades with permeable leading edges under disturbed inflow conditions was performed. The airfoils and fan blades with permeable leading edges were made of an aluminum alloy using a powder bed fusion-based additive manufacturing process. In a first step, a wind-tunnel study was carried out. This consisted of detailed aerodynamic and aeroacoustic measurements on 16 airfoils with different permeable leading-edge de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 77 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Further works have showed the potential of porous materials for noise reduction [9,16,[26][27][28][29][30][31][32], but a common conclusion is found that better understanding of the mechanisms and flow interaction is needed to optimize the implementation of porous materials for the noise abatement. An effort to address the understanding behind the flow mechanisms has had more consideration in recent years [33][34][35][36][37]. Zamponi et al [34] studied a melamine foam airfoil and the effect on turbulence distortion near the airfoil leading edge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further works have showed the potential of porous materials for noise reduction [9,16,[26][27][28][29][30][31][32], but a common conclusion is found that better understanding of the mechanisms and flow interaction is needed to optimize the implementation of porous materials for the noise abatement. An effort to address the understanding behind the flow mechanisms has had more consideration in recent years [33][34][35][36][37]. Zamponi et al [34] studied a melamine foam airfoil and the effect on turbulence distortion near the airfoil leading edge.…”
Section: Introductionmentioning
confidence: 99%
“…Zamponi et al [34] studied a melamine foam airfoil and the effect on turbulence distortion near the airfoil leading edge. Ocker et al [33] considered a wide range of porous structures for permeable leading edge airfoils to systematically study the effect of the porous structure on turbulence interaction noise and fan noise. Palleja-Cabre et al [36] and Priddin et al [38] experimentally and analytically studied a flat plate in a turbulent stream in a two part study.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of reducing turbulence interaction noise, different leading-edge modifications have been developed that affect the aerodynamic and aeroacoustic properties of axial fans. Leading-edge treatment approaches to reduce turbulence interaction noise for axial fans include leading-edge serrations [3][4][5][6][7][8], flow-permeable materials [9][10][11] or modifications of the blade shape in the form of sweeping or skewing [12][13][14][15][16][17]. The approach followed in this work is based on preliminary wind tunnel investigations on slitted flat-plate airfoils [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Such an idea was later extended to cascade blades in order to reduce aero-engine noise (de Sousa 2011; Ocker et al. 2021). In particular, a soft vane structure, which provides soft boundaries on fan stator vanes with reasonably small aerodynamic loss, is proposed by NASA (Elliott, Woodward & Podboy 2009; Jones et al.…”
Section: Introductionmentioning
confidence: 99%
“…As a convenient way to introduce soft boundaries, porosity was first applied to a single aerofoil and studied both numerically (Tinetti 2001;Teruna et al 2020Teruna et al , 2021 and experimentally (Geyer, Sarradj & Fritzsche 2010;Sarradj & Geyer 2014;Chaitanya et al 2020). Such an idea was later extended to cascade blades in order to reduce aero-engine noise (de Sousa 2011; Ocker et al 2021). In particular, a soft vane structure, which provides soft boundaries on fan stator vanes with reasonably small aerodynamic loss, is proposed by NASA (Elliott, Woodward & Podboy 2009;Jones et al 2009;Jones & Howerton 2016) to reduce rotor-stator interaction noise, and its experiments have shown promising results for potential applications in a real aero-engine.…”
Section: Introductionmentioning
confidence: 99%